Os recursos humanos e a gestão pela qualidade total - Reali, José Luiz Soares (2004)
In the present work, we observe that total quality is an organizational way of life, a new way to do things, a revolution in how organizations work with their employees, surpassing the mere technical vision of business administration. Times when you only had to administrate finance, technology, people and process are ended. We need to create a work environrnent which motivated everybody to contribute with the organization in search of total quality. Nowadays, the formulation of human resources public politics, already integrated with the objectives of any organization, are indispensable and fundamental in our search for excellency and reach of high levels of productivity. During this work we exposed origin and development of thinking chains which form total quality concepts as well as human resources development and planning repercussion in the organization structure and economy globalization process consequences. Finally, we developed a research which demonstrate how far total quality concepts are present in the human resources department of Brazilian Superior Courts.